2017
DOI: 10.1038/ajg.2017.282
|View full text |Cite
|
Sign up to set email alerts
|

Yes, We Are Still Talking about Cylosporin vs. Infliximab in Steroid Resistant Acute Severe Ulcerative Colitis

Abstract: The Spanish IBD Registry (ENEIDA) is reporting in this issue of the Journal on a retrospective assessment of outcomes of cyclosporine use and infl iximab use to treat steroid refractory acute severe ulcerative colitis (SR-ASUC) between 1989 and 2013. Overall, they found similar outcomes in terms of 3 month and 1 year colectomy rates. Serious adverse events were lower in cyclosporine users. While this study does not meet the standard of a prospective randomized controlled trial, it does remind us that cyclospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Despite its methodological issues, this large cohort again showed no difference in colectomy rate between cyclosporin and infliximab therapy (respectively 19.6% and 23.6%, p=0.57 at 1 year) with severe adverse events and infection being more common in the infliximab group. 34,35 However, a recent prospective cohort study in 55 ASUC patients showed higher endoscopic remission rates in infliximab treated patients compared to patients treated with cyclosporine (73% vs 25%). 36 Korean ASUC patients treated showed better colectomy rates with infliximab then previously described (eg, 6.9% at 3 months and 18.1% at a mean follow-up of 69 months).…”
Section: Challenge 2: Current Treatment Strategies Of Asuc Are Based mentioning
confidence: 99%
“…Despite its methodological issues, this large cohort again showed no difference in colectomy rate between cyclosporin and infliximab therapy (respectively 19.6% and 23.6%, p=0.57 at 1 year) with severe adverse events and infection being more common in the infliximab group. 34,35 However, a recent prospective cohort study in 55 ASUC patients showed higher endoscopic remission rates in infliximab treated patients compared to patients treated with cyclosporine (73% vs 25%). 36 Korean ASUC patients treated showed better colectomy rates with infliximab then previously described (eg, 6.9% at 3 months and 18.1% at a mean follow-up of 69 months).…”
Section: Challenge 2: Current Treatment Strategies Of Asuc Are Based mentioning
confidence: 99%
“…In the multivariate analysis, the use of two or more of these agents in addition to CyA was associated with a significantly higher rate of opportunistic infection (OR 14.5, 95% CI 4.9-43) compared to only one additional agent (OR 2.9, 95% CI 1.5-5.3) [27,34]. Furthermore, total cholesterol should be greater than 170 to avoid 3% risk of seizures with drug administration [6,35]. Given these side effects, CyA needs to be used with caution, carefully monitoring serum CyA levels and renal function as well as for potentially life-threatening infectious complications.…”
Section: Infliximab and Cyclosporinementioning
confidence: 99%
“…Check levels at 2 weeks, and if less than 25, consider administering the third induction dose at week 4 instead of week 6. Consider adding a thiopurine when the steroid dose has been reduced below 20 mg. Plan to keep him on the thiopurine for less than 2 years as the risk of hepatosplenic T cell lymphoma is highest in his demographic (males <age 35).…”
Section: Other Approaches To Considermentioning
confidence: 99%